Requirement of Drosophila I(2)gl function for survival of the germline cells and organization of the follicle cells in a columnar epithelium during oogenesis. - Lorenzo, Cécilia de; Strand, Dennis; Mechler, Bernard (The international journal of developmental biology, 1999)
The lethal(2)giant larvae gene, or 1(2)gl, encodes a widely expressed cytoskeletal protein which acts in numerous biological processes during embryogenesis and oogenesis, including cell proliferation, and morphogenetic movements. Having identified the nucleotide change occurring in the l(2)gl(ts3) sequence, we produced by site-directed mutagenesis the identical change leading to the substitution of a serine by a phenylalanine at position 311 of p127l(2)gl and introduced the modified l(2)glF311 gene into l(2)gl flies. The transgene can fully rescue the development of l(2)gl flies raised at 22 degrees C but causes drastic effects on their development at 29 degrees C confirming the temperature sensitivity of the phenylalanine substitution at position 311. Fertility of females, albeit not of males, was strongly affected. Temperature-shift experiments and microscopic examination of ovaries showed that the mutation blocked egg chamber development at the onset of vitellogenesis (stages 8-9) with growth arrest of the oocyte, incomplete follicle cell migration over the oocyte associated with abnormal organization of the follicular epithelium, and apoptosis of the germline cells, as measured by TUNEL assays. By comparison to wildtype, we found that p127F311 is already reduced in amount at 22 degrees C and delocalized from the cytoskeletal matrix, albeit without affecting the apical localization of myosin II, a major partner of p127. At 29 degrees C, the level of p127F311 is even more reduced and the distribution of myosin-II becomes markedly altered at the apices of the follicle cells. These data indicate that during oogenesis p127 plays a critical function at the onset of vitellogenesis and regulates growth of the oocyte, follicle cell migration over the oocyte and their organization in a palisadic epithelium, as well as viability of the germline cells.